Capital ownership, innovation and regional development policy in the economic periphery: An energy industry case. (September 2020) - Jones, Calvin; Munday, Max
This paper examines how far patterns of external ownership affect benefits from industry geographical proximity. The case explores investments in energy and electricity supply in Wales. Geographically related benefits are examined through a Smart Specialisation lens, in the areas of innovation; firm-to-firm interaction; the labour market and public sector intervention. We find evidence that the ownership model or 'home location' of key firms is an important factor driving local economic benefits, and explore related policy implications. The case shows that the location of ownership is a key factor in firm innovative behaviour, and that the scale and nature of any benefits from industry geographical proximity will be dependent on where key decision centres lay. In spite of Wales' comparative advantage in energy, the paper reveals no dynamic 'melt' of interactive and engaged firms and labour, but a functionally narrow, low value economic landscape. This leads to a request for more focus on the ownership and contextual factors that may drive the benefits of industrial proximity for places.